Faktor - Faktor Yang Berhubungan Dengan Kualitas Handover Pasien Di Ruang Rawat Inap Rumah Sakit - Sulistyawati, Wiwin (Universitas Muhammadiyah Surabaya, 2020)
The purpose is to know the factors related to the quality of the patient’s handover in inpatient room of the hospital. This research is a correlational analysis study with a cross sectional approach. Data retrieval uses questionnaires and observation sheets. The number of samples on this study is 79 nurses taken in random sampling techniques. Statistical analysis used is a test of spearman rank. The results show that most of the respondents (69.6%) are diploma graduates, and 72.2% of respondents have a working time of < 5 years. Almost all respondents (93.7%) have good motivation, and 94.9% of respondents have good handover quality. The last educational variable (p = 0.388) and the nurse’s working time (P = 0.209) are not related to the quality of the handover, while the motivation (P = 0.000) and the implementation of the chief nurse’s supervision (P = 0.000) relate to the quality of the handover between the shifts in the inpatient room of the hospital. The conclucion of this study is the motivation and the implementation of the chief nurse’s supervision relate to the quality of the handover between the shifts in the inpa- tient room of the hospital. Hospital’s management is expected to raise the motivation of nurses in conducting handover and enhancing the supervision of the chief nurse to improve the quality of the patient’s handover and minimize the errors in information exchange conducted by nurses.